The Effect of Ocular and Systemic Factors on Ocular Pulse Amplitude - Uzun, İrfan (Fırat University, 2012)
Objective: To assess the effect of ocular and systemic factors on ocular pulse amplitude in patients with primary open angle glaucoma. Materials and Methods: Fifty eyes of 50 primary open angle glaucoma patients were included in this study. Patients underwent routine ophthalmologic examination with intraocular pressure and ocular pulse amplitude measurement by Pascal dynamic contour tonometry and perimetry by Octopus automatic perimeter. The factors related to ocular pulse amplitude were statistically evaluated. Results: The mean age of the patients was 63±9,76 years. Of 50 patients, 29(58%) were female and 21(42%) were male. The mean ocular pulse amplitude, intraocular pressure, age, duration of glaucoma, MD(mean deviasyon) and sLV(loss variance) of perimetry measurement were as follows; 2,87±0,86 mmHg, 17,01±2,59 mmHg, 63±9,76 year, 32,7±46,92 month, 6,06±3,7, 4,23±1,55. There was no correlation between ocular pulse amplitude and age, gender, systemic disease, visual acuity, duration of glaucoma, glaucoma drugs, MD and sLV(p>0.05). Ocular pulse amplitude showed statistically significant positive correlation with intraocular pressure (p=0,003). Conclusion: Ocular pulse amplitude was demonstrated to have significant association with intraocular pressure.

Amaç: Primer açık açılı glokomu olan hastalarda oküler ve sistemik faktörlerin oküler nabız genliği üzerine olan etkisini araştırmak. Gereç ve Yöntem: Primer açık açılı glokomu olan 50 hastanın 50 gözü çalışmaya alındı. Hastaların rutin oftalmolojik muayeneleri, Pascal tonometresi ile göz içi basıncı ve oküler nabız genliği ölçümü, Octopus otomatik perimetresi ile görme alanı ölçümü yapıldı. Oküler nabız genliği ile ilişkili faktörler istatistiksel olarak değerlendirildi. Bulgular: Hastaların yaş ortalaması 63±9,76 yıl idi. Hastaların 29'u (%58) kadın, 21'i (%42) erkek idi. Hastaların oküler nabız genliği, göz içi basıncı, yaş, glokomun süresi ve görme alanı ölçümleriyle elde edilen MD(mean deviasyon) ve sLV(loss variance) ortalama değerleri sırasıyla 2,87±0,86 mmHg, 17,01±2,59 mmHg, 63±9,76 yıl, 32,7±46,92 ay, 6,06±3,7, 4,23±1,55 olarak saptandı. Yaş, cinsiyet, sistemik hastalıklar, görme keskinliği, glokumun süresi, glokom ilaçları, MD ve sLV değerlerinin oküler nabız genliğini etkilemedikleri bulundu (p>0.05). Göz içi basıncı ile oküler nabız genliği arasında ise istatistiksel olarak anlamlı derecede pozitif korelasyon olduğu bulundu( p=0,003). Sonuç: Oküler nabız genliği ile göz içi basıncı arasında anlamlı bir ilişki olduğu gösterildi.
Oküler ve Sistemik Faktörlerin Oküler Nabız Genliği Üzerine Olan Etkisi